Introducing “captaining”: How to best combine group work with individual achievement within higher education examination - Mirek Dymitrow (Journal of Pedagogical Research, 2020)
This paper deals with the problem of making group work and individual achievement meet in the context of combined examination at universities. The underlying idea of this research derives from the policy that is increasingly gaining power at many university departments, namely that it is inappropriate to examine students on the basis of group work alone, while at the same time limited departmental resources cannot allow for increasing the number of individual examinations. This paper attempts to square this paradox by elaborating on new ways to individualize compulsory group work so that it fulfils both formal and educational objectives, but also so it feels meaningful, motivative and fair to the students. This multifaceted challenge is captured in a novel methodological approach named “captaining”. By drawing on existing theoretical frameworks, own experiences and subsequent evaluation, “captaining” is presented as a promising alternative to the individualism vs. collectivism dilemma, as well as to extra-educational factors impacting the implementation of best examination practices.